Superficial Retinal Microvasculature and Choriocapillaris Alterations after Photodynamic Therapy in Chronic Central Serous Chorioretinopathy - Morteza Entezari; Iman Ansari; Alireza Ramezani; Humayoun Nikkhah; Parisa Mohammadi; Bahar Kheiri (Journal of Ophthalmology, 2022)
Purpose. To compare superficial retinal vascular, choriocapillaris (CC), and choroidal thickness changes in chronic central serous chorioretinopathy (CSCR) patients after half-dose photodynamic therapy (PDT). Method. In this prospective interventional case series study, fifteen eyes of 14 patients with chronic CSCR undergoing half-dose PDT treatment were enrolled. All patients underwent enhanced depth imaging optical coherence tomography angiography (EDI-OCT) and optical coherence tomography angiography (OCTA) at baseline and 3 months after treatment. Best-corrected visual acuity (BCVA), superficial retinal vascular density, CC vessel density, foveal avascular zone (FAZ), central macular thickness (CMT), and choroidal thickness were compared. Results. Mean BCVA before and after PDT was 0.34 ± 0.26 and 0.19 ± 0.25 logMAR, respectively (p=0.011). Mean FAZ before treatment was 410.21 ± 117.00 μm2, which increased to 433.50 ± 116.76 μm2 (P=0.253). Mean vessel density at superficial capillary plexus (SCP) was 38.93 ± 11.12 at baseline, which increased to 39.04 ± 11.43 (P=0.886). Mean CC vessel density was 53.21 ± 4.14 at baseline, which significantly decreased to 51.85 ± 4.21 (P=<0.001). BCVA has no significant correlation with FAZ (P=0.282) and vessel density (P=0.0.241) at SCP. CMT significantly decreased from 380.87 ± 41.66 μ at baseline to 268.20 ± 28.07 μ at 3 months (P=0.132). We did not find any correlation between CMT and FAZ (P=0.040) and vessel density (P=0.686) at SCP. Mean subfoveal choroidal thickness reduced from 411 ± 171 μm before treatment to 372 ± 117 μm (P=0.106). Conclusion. PDT treatment can affect retinal and choroidal structural parameters, but we could not find any significant influence on retinal vascular parameters, including FAZ area and vessel densityonly mean CC vessel density and subfoveal choroidal thickness decreased.